EUGLYCAEMIC DIABETIC KETOACIDOSIS AS A CAUSE OF REFRACTORY METABOLIC ACIDOSIS IN A PREGNANT PATIENT - WA, Siti Sanaa; MA, Masliza Hanuni; MK, Firdaus (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Euglycemic diabetic ketoacidosis (DKA) in pregnancy is a rare obstetric emergency that may lead to substantial morbidity and mortality to both the mother and foetus. Prompt recognition is challenging due to misleading euglycemic state. The risk for euglycaemic DKA increases during the second half of pregnancy due to the higher levels of hormones with anti-insulin effects, increase in insulin demand, combined with exhausted glycogen stores. CASE We report a case of a 33-year-old female G3P2 at 33 weeks AOG, admitted for fever, cough, vomiting and poor oral intake for three days. Antenatally, she had GDM and was well-controlled on metformin. On arrival she was tachycardic with HR of 106 bpm, and tachypnoeic with RR 28/min, requiring 5 L oxygen. There were coarse crepitations over the right lower and mid-lung field. Her laboratory results showed TWBC of 6.5 x 109 /L, hypokalaemia (3.0 mmol/l) and mild metabolic acidosis (pH 7.43, HCO3 18.8 mmol/l). CXR revealed consolidation over the right lower zone. CTPA excluded pulmonary embolism. Her clinical condition deteriorated with serial blood gases in the ward showing worsening and persistent metabolic acidosis (pH 7.284, HCO3 12.9 mmol/l, pCO2 20.5, lactate 1.1 mmol/l) with an anion gap of 12. Her glucose readings were within the normal range, 5.3-5.9 mmol/L. We arrived at a diagnosis of euglycaemic DKA only when the urine ketone came back as ++ and blood ketone was 3.5 mmol/L. From here, IV Dextrose 10% boluses were given with 104 ml/hour maintenance over 24 hours. Concurrently, she was started on fixed-dose insulin infusion which was intensified accordingly. Ketoacidosis resolved and she was discharged well with SC levemir 8 units ON. Conclusion Our case highlights that it is imperative for the treating physician to have a high index of suspicion of this condition, so as to not delay lifesaving management.